Increasing the Efficiency of Cattle Bone Ash P Fertilization with Nano Technology and Its Effect on the Growth and Yield of Shallots - Hidayat, Taufiq; Widyastuti, Titiek; Wulandari, Fetty Nur Cahyati; Dewi, Sukuriyati Susilo (PLANTA TROPIKA, 2023)
The study investigates the efficacy of nano-sized cattle bone ash as an alternative phosphorus source for shallot cultivation, aiming to reduce dependence on mined phosphate rock. The experimental study was arranged in a 4 x 3 factorial Completely Randomized Design. The first factor was the recommended dose of P fertilizer, consisting of 100%, 80%, 60%, and 40%. The second factor was using nano cattle bone ash as a foliar application, applied 3, 4, and 5 times. The observation was made on the plant growth and yield of shallot. Data analysis was conducted with an ANOVA and continued with the DMRT. The results showed no interaction effect of the dose of P fertilizer and the frequency of spraying nano cattle bone ash on the growth and yield of shallots. The application of P fertilizer at 40% of the recommended dose could already produce shallots that were the same as the application of P fertilizer according to the recommended dosage. The spraying frequency of three times was able to provide high shallot yields.  In the future, it is expected that spraying cow bone ash with nanotechnology can be applied three times with a 40% recommended dose of P to increase fertilization efficiency.